The law firm of the future : adapting to a changed legal marketplace - Westcott, John M. (Edward Elgar Publishing, 2018)
During the "golden age of law firm growth" from the late 1960s until 2007, most large law firms adopted a default growth strategy, increasing practice areas and offices, aided by the momentum of the tail winds of law firm growth. Since the recession of 2008-2009, however, the legal marketplace has drastically changed. The market has become too sophisticated for undifferentiated large firms, and in this timely book, Jay Westcott suggests strategic building blocks that firms can adopt in order to adapt themselves to this radical change and prosper as lasting institutions. In order to counteract client pushback, firms must concentrate on their market strengths, and clients will differentiate firms by price, size, and expertise. This book will serve as a critical resource for law firm partners and managers who are interested in developing successful, distinctive firms. Law scholars will also be interested in this examination of the profession and how it is changing, as will clients and businesses.